College Major Restrictions and Student Stratification - Zachary Bleemer; Aashish Mehta (CESifo GmbH, 2024)
Underrepresented minority (URM) college students have been steadily earning degrees in relatively less-lucrative fields of study since the mid-1990s. A decomposition reveals that this widening gap is principally explained by rising stratification at public research universities, many of which increasingly enforce GPA restriction policies that prohibit students with poor introductory grades from declaring popular majors. We investigate these GPA restrictions by constructing a novel 50-year dataset covering four public research universities' student transcripts and employing a staggered difference-in-difference design around the implementation of 29 restrictions. Restricted majors' average URM enrollment share falls by 20 percent, which matches observational patterns and can be explained by URM students' poorer average precollege academic preparation. Using first-term course enrollments to identify students who intend to earn restricted majors, we find that major restrictions disproportionately lead URM students from their intended major toward less-lucrative fields, driving within-institution ethnic stratification and likely exacerbating labor market disparities.
Keywords: H75; I24; J31; Z13; 330; higher education; racial wage gap; college majors